Effect of principal instructional leadership on teacher commitment - Sucitra, Diah Ayu; Hariri, Hasan; Riswandi, Riswandi (Intelektual Pustaka Media Utama, 2024)
A comprehensive examination of the impact of instructional leadership provided by school principals on teacher commitment was carried out across different nations, including Indonesia. This research employed a literature review approach, scrutinizing journal articles that delved into the connection between the instructional leadership of school principals and teacher commitment. After applying predefined criteria to 120 chosen articles in this domain, only 15 articles met the specified criteria and were subsequently incorporated into the review. The findings of the literature review revealed that the instructional leadership of school principals and the resulting organizational commitment have a positive, and mostly said statistically significant, effect on teacher organizational commitment in various countries.